The Relationship between the Existence of Aedes aegypti Breeding Places, PSN, and DHF in Oesapa Village - Yeni Horo; Pius Weraman; Agus Setyobudi (Lontar : Journal of Community Health, 2022)
Dengue hemorrhagic fever (DHF) is an acute febrile disease caused by the dengue virus. Indonesia has relatively high cases of DHF, and DHF outbreaks often occur. Various efforts and prevention programs have been carried out, but DHF increases every year. This study aimed to analyze the relationship between mosquito larvae breeding sites and mosquito nest eradication (PSN) with the incidence of DHF in the Oesapa Village, Kupang City, Kelapa Lima District. This research was quantitative research using a cross-sectional study. The research sample was 95 families taken using simple random sampling and the Lemeshow formula. The data was analyzed univariable and bivariable using the chi-square test. The results showed that the factors associated with the incidence of DHF were mosquito larvae breeding sites (p-value = 0.005) and PSN (p-value = 0.014). Implementing 3M Plus movement is necessary to eradicate mosquito larvae, namely draining, closing, and burying. The pluses are using mosquito repellent, mosquito nets, and avoiding the habit of hanging clothes in the house, which can be a mosquito-resting place.